The Influence of the Project Based Learning Model on Students' Learning Outcomes in Statistics - Siska Febryana; Liknin Nugraheni (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2023)
Based on the preliminary study conducted by the researchers in the field, there has been a decrease in students' learning outcomes at SMA Kartika Surabaya due to the prolonged implementation of online learning. Therefore, this research aims to enhance understanding by investigating the influence of the Project Based Learning Model on students' learning outcomes in statistics. The research employs a quantitative statistical analysis. The sampling where twelfth class of natural science 1 as the experimental group and twelfth class of natural science 2 as the control group. The data were collected using test based on students' learning outcomes and analysed for normality, homogeneity, and hypothesis testing. The results showed that the average learning outcomes of students taught using the Project-Based Learning Model are higher than those taught using the conventional model. The results of the hypothesis test using the independent sample t-test with a significance value (sig.) of 0.004 < α = 0.05, indicating H0 was rejected and H1 was accepted. Based on the research findings, it can be concluded that there is an influence of the project-based learning model on students' learning outcomes in statistics for twelfth class of natural science at SMA Kartika IV-3 Surabaya.